Systemic lupus erythematosus associated with sickle-cell disease: a case report and literature review - Maamar Mouna; Tazi-Mezalek Zoubida; Harmouche Hicham; Mounfaloti Wafaa; Adnaoui Mohammed; Aouni Mohammed (Journal of Medical Case Reports, 2012)
Abstract Introduction The occurrence of systemic lupus erythematosus has been only rarely reported in patients with sickle-cell disease. Case presentation We describe the case of a 23-year-old North-African woman with sickle-cell disease and systemic lupus erythematosus, and discuss the pointers to the diagnosis of this combination of conditions and also present a review of literature. The diagnosis of systemic lupus erythematosus was delayed because our patient’s symptoms were initially attributed to sickle-cell disease. Conclusions Physicians should be alerted to the possible association of sickle-cell disease and systemic lupus erythematosus so as not to delay correct diagnosis and initiation of appropriate treatment.